2008
DOI: 10.1177/0310057x0803600315
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Changes Associated with Intubation with the Intubating Laryngeal Mask Airway Compared with Conventional Laryngoscopy

Abstract: This open, prospective, randomised study was designed to evaluate the changes in intraocular pressure and haemodynamics after tracheal intubation using either the intubating laryngeal mask airway (ILMA) or direct laryngoscopy. Sixty adult patients, ASA physical status 1 or 2 with normal intraocular pressure were randomly allocated to one of the two techniques. Anaesthesia was induced with propofol followed by rocuronium. Tracheal intubation was performed using either the ILMA or Macintosh laryngoscope. Intraoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Some pre-treatments (lignocaine pre-treatment either intravenous or nebulised, or intranasal nitroglycerine) have been used to attenuate ocular and systemic responses to prevent increase in IOP associated with tracheal intubation. Laryngeal mask airway has been proposed as an alternative to endotracheal tube [10,12,13]. …”
Section: Discussionmentioning
confidence: 99%
“…Some pre-treatments (lignocaine pre-treatment either intravenous or nebulised, or intranasal nitroglycerine) have been used to attenuate ocular and systemic responses to prevent increase in IOP associated with tracheal intubation. Laryngeal mask airway has been proposed as an alternative to endotracheal tube [10,12,13]. …”
Section: Discussionmentioning
confidence: 99%
“…The highest mean of IOP before the procedure 18 [ 17 ] and after the procedure 20.5 [ 18 ] was seen in the ETT group. On the other hand, the lowest mean changes before and after the procedure were found in the ETT group and the LMA group, respectively [ 19 ]. In this meta-analysis, two population categories were represented: two studies were from the pediatrics population and four studies were from the adult population (Tables 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, subgroup analysis of this systematic review and meta-analysis revealed that the pooled standard mean differences of IOP in adult and pediatric population showed that higher standard mean differences were found in adult populations 1.702 (95% CI, 1.048, 2.356) as compared to pediatric populations 0.535 (95% CI, 0.129, 0.941). Furthermore, most studies conducted to determine the effects of endotracheal intubation and laryngeal mask airway insertion indicated that laryngeal mask airway has a lesser intraocular pressor response [ 7 , 17 19 , 25 , 26 ]. Another study done to measure the change in intraocular pressure on both right and left eyes showed that both groups were associated with significant intraocular pressor responses; nevertheless, the mean maximum increase was significantly higher after tracheal intubation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain's laryngeal mask airway and intubating laryngeal mask airway have shown a clear advantage over direct laryngoscopy for tracheal intubation in minimizing increase in IOP with lesser sympathetic stimulation than endotracheal tube insertion. [ 1 6 ] Takahashi et al . [ 7 ] compared conventional laryngoscope with Lightwand intubating device (Trachlight) for hemodynamic changes, but could not find any difference in response.…”
Section: Discussionmentioning
confidence: 99%